Zaburzenia własnej tożsamości jako wyraz patologii... - Grochmal- Bach, Bożena (Horyzonty Wychowania, 2017)
The author takes up the issues connected with human psyche,particularly with identity disorders with reference to mentalhealth. That is why, her discussion starts with defining basicterms such as identity, consciousness, identity consciousnessand „ego/self”. The definitions of these notions appear not uniformin the literature of the subject.The author’s reflections are largely based on the, so-called,microgenetic theory, which assumes that every single human behaviourin a given moment constitutes the culmination of thewhole evolution process of evolution. Microgenesis is the nextphase of evolution on a time scale, after phylogeny andontogenesis.The concept of identity is presented in five different aspects.In the physical sense, identity is understood as continuity ofbodily existence, i.e. DNA. In legal aspect, identity, primarily,consists in being alone. In sociology, the idea of identity of specificsocial groups is developed. Whereas identity in psychologicalsense has various meanings, however, the most importantissue seems the fact that possessing psychological identityrequires a relatively healthy brain; it does not exist outside humanconsciousness. Explaining identity in theological aspect, theauthor refers to Karol Wojtyła’s views.